Fast charging negative electrodes based on anatase titanium dioxide beads for highly stable Li-ion capacitors. (June 2020) - Calcagno, G.; Lotsari, A.; Dang, A.; Lindberg, S.; Palmqvist, A.E.C.; Matic, A.; Cavallo, C.
Abstract: Hybrid energy storage systems aim to achieve both high power and energy densities by combining supercapacitor-type and battery-type electrodes in tandem. The challenge is to find sustainable materials as fast charging negative electrodes, which are characterized by high capacity retention. In this study, mesoporous anatase beads are synthetized with tailored morphology to exploit fast surface redox reactions. The TiO2 -based electrodes are properly paired with a commercial activated carbon cathode to form a Li-ion capacitor. The titania electrode exhibits high capacity and rate performance. The device shows extremely stable performance with an energy density of 27 mWh g - 1 at a specific current of 2.5 A g −1 for 10, 000 cycles. The remarkable stability is associated with a gradual shift of the potential during cycling as result of the formation of cubic LiTiO2 on the surface of the beads. This phenomenon renews the interest in using TiO2 as negative electrode for Li-ion capacitors. Graphical abstract: Image 1 Highlights: Hybrid energy storage system. Titanium dioxide anatase mesoporous anode. Activated carbon. Hybrid asymmetric supercapacitor. High stability Li-ion capacitor.